ANALISA PENERAPAN APLIKASI PENJUALAN DAN SERVICE KOMPUTER PADA CV JAYA CITRA MADANI DENGAN METODE TECHNOLOGY ACCEPTABLE MODEL (TAM) - Alief Rizky Dharmawan; Sri Hariyati Fitriasih; Tri Irawati (STMIK Sinar Nusantara, 2018)
CV Jaya Citra Madani is one of the businesses engaged in services of computer service and computer spare parts sales. Currently there is no standard measuring tool to measure the application of sales. This study aims to apply the Technology Acceptable Model (TAM) method measures the use of sales applications especially on the user interface program and ease of use of the application. The result that the interface design and user behavior had an effect on the real condition of the users with the respective values of 0,644 and 0,988. While the use and attitude have no effect on the real condition of users with the respective values of -0,002 and -0,444.